Engineering materials 2 an introduction to microstructures and processing - Ashby, M. F. (Butterworth-Heinemann, 2013)
Suitable for advanced students of materials science and mechanical engineering, this book provides a concise introduction to the microstructures and processing of materials and shows how these are related to the properties required in engineering design.